1997
DOI: 10.1046/j.1365-3083.1997.d01-384.x
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin‐7 (IL‐7) in Colorectal Cancer: IL‐7 is Produced by Tissues from Colorectal Cancer and Promotes Preferential Expansion of Tumour Infiltrating Lymphocytes

Abstract: Despite increasing survival rates for patients with colorectal cancer, additional treatment options are required, including active or passive immunotherapy for patients with metastatic disease. Freshly harvested colorectal cancer specimens and in vitro cultured colorectal cancer cell lines were examined for IL-7 protein secretion in order to examine the potential role of this cytokine in the interaction between tumour cells and the host immune system. Freshly harvested colorectal cancer specimens (21/21), or n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(39 citation statements)
references
References 40 publications
1
38
0
Order By: Relevance
“…IL-7 values have been associated with bone metastatic disease and hematological malignancies [8][9][10]. Different levels of IL-7 have been measured in renal [11], neuroblastoma [12], glioma [13], colorectal [14], central nervous system, and lung cancers [15], however; until now no clear conclusions had been drawn in regards to how these values influence tumor progresIvyspring International Publisher sion. It has also been observed that IL-7 is responsible for osteoclastogenesis through fusion with macrophage colony stimulating factor (M-CSF), binding with tumor necrosis factor-α (TNF-α) and receptor activator of nuclear factor-α (RANKL) [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…IL-7 values have been associated with bone metastatic disease and hematological malignancies [8][9][10]. Different levels of IL-7 have been measured in renal [11], neuroblastoma [12], glioma [13], colorectal [14], central nervous system, and lung cancers [15], however; until now no clear conclusions had been drawn in regards to how these values influence tumor progresIvyspring International Publisher sion. It has also been observed that IL-7 is responsible for osteoclastogenesis through fusion with macrophage colony stimulating factor (M-CSF), binding with tumor necrosis factor-α (TNF-α) and receptor activator of nuclear factor-α (RANKL) [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…IL-7 has also been described to be alternatively spliced. [8][9][10][11] This is not driven by allelic variants of the human IL-7 gene, located on chromosome 8q12-13. IL-7 splice variants have been identified in different conditions: malignant transformation, 9 exposure to proinflammatory cytokines and tissue/organspecific expression.…”
Section: Introductionmentioning
confidence: 99%
“…Recent results suggested that IL-7 does not result in nonspecific alterations of the T-cell population but, rather, exerts a homeostatic effect by increasing the number of antigen-specific T cells (8). Therefore, differences in the TCR composition of TIL observed in this report may also reflect the antigen-driven expansion of certain TCR VA and VB subsets which may have already been selected for IL-7-dependent growth in vivo (20). In addition, gain of TIL effector function may not be correlated with expansion of certain TCR families (8).…”
Section: Vol 9 2002 T-cell Selection In Patients With Cervical Cancmentioning
confidence: 55%